The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1046/j.1464-410x.2002.02890.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated renal haemangioma in children: presentation and management

Abstract: A 28-day-old baby boy presented with progressive jaundice and pallor of 3 weeks' duration. On examination he had moderate abdominal distension with a large rightsided firm immobile abdominal mass reaching the right iliac fossa. Laboratory studies showed severe anaemia (haemoglobin 52 mg/L), thrombocytopenia (platelet count 26 000/ µ L) and unconjugated hyperbilirubinaemia (total/direct bilirubin 193/7mg/L); Coombs test was negative. CT of the abdomen revealed a 10 × 7.5 × 5.5 cm heterogeneous mass arising from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…A summary of the 50-year literature of pediatric renal vascular tumor cases (exclusive of malformations) is provided in Table 1. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The list includes recent histologic diagnoses which are either provisionally or not yet incorporated in the International Society for the Study of Vascular Anomalies (ISSVA) classification system. 23 One of the uncategorized lesions is anastomosing hemangioma, which was recently described and has since been increasingly reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of the 50-year literature of pediatric renal vascular tumor cases (exclusive of malformations) is provided in Table 1. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The list includes recent histologic diagnoses which are either provisionally or not yet incorporated in the International Society for the Study of Vascular Anomalies (ISSVA) classification system. 23 One of the uncategorized lesions is anastomosing hemangioma, which was recently described and has since been increasingly reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated cavernous haemangioma was reported in the right kidney of a newborn, who presented with moderate abdominal distension and a large abdominal mass reaching to right iliac fossa 5 . Rastogi R et al reported a vesical haemangioma at VUJ in a patient with abdominal pain secondary to hydroureteronephrosis 6 .…”
Section: Discussionmentioning
confidence: 96%
“…Organs like kidney are rarely involved and bilaterality is still rarer. [1–4] Multiple hemangiomas in the same kidney occur in upto 12 % cases. [4] Renal hemangiomas may vary in size from few millimeters to several centimeters in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Sometimes renal hemangioma is a manifestation of a generalized hemangiomatosis that is they are associated with hemangiomas in liver, bowel, bone, or brain. [5] Patients usually present with profuse or relapsing painless gross hematuria, sometimes pain may be present, which mimics renal colic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation